HUBUNGAN TINGKAT KESEGARAN JASMANI DENGAN KECERDASAN SISWA KELAS VII SMP PEMBANGUNAN LABORATORIUM UNIVERSITAS NEGERI PADANG - Siska Siska (JURNAL PENDIDIKAN ROKANIA, 2019)
This research aims to know the level of intelligence of students of grade VII SMP Development Laboratory of Padang State University, the level of physical freshness of class VII students SMP Development Laboratory of Padang State University, and relationship level Physical freshness with the intelligence of class VII SMP Pembangunan Laboratories of Padang State University. This research is correlational. The population is a grade VII student of the Padang State University laboratories which amounted to 203 people. Sampling techniques are purposive sampling with a total of 30 people. To measure the level of physical freshness used TKJI test (Indonesian physical freshness test) for sons and daughters aged 13-15 years and the assessment of Intelligence (IQ) is obtained from the Intellegence (IQ) test in cooperation with the Department of Counseling Faculty of Science Education UNP. Data analysis is done using SPSS 13.0. Based on the results of research findings known average (mean) physical freshness of 12.87 and its deviation (Stardar deviation) 2.12, while the average Intellegence (IQ) is 96.77 and its deviation is 6.93. From the results of a correlation analysis of research acquired correlation coefficient r = 0.394 with significance level 0.031 meaning that there is a significant relationship between the level of physical freshness with the intelligence of junior secondary students development class VII Padang State University Laboratory.